2021
DOI: 10.1098/rstb.2020.0090
|View full text |Cite
|
Sign up to set email alerts
|

The replaceable master of sex determination: bottom-up hypothesis revisited

Abstract: Different group of vertebrates and invertebrates demonstrate an amazing diversity of gene regulations not only at the top but also at the bottom of the sex determination genetic network. As early as 1995, based on emerging findings in Drosophila melanogaster and Caenorhabditis elegans , Wilkins suggested that the evolution of the sex determination pathway evolved from the bottom to the top of the hierarchy. Based on our current knowledge, this review revisits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Interestingly, with only a handful of exceptions (4 out of 12, table 1), the great majority of MSD genes belonging to the TGF-β family pathway arose via GD (table 1). Under this scenario, following a sudden duplication event, gradual neutral processes are thought to act on the dispensable gene copy (see the documented example of Dmrt1bY in medaka for instance, [15,48,49]). One of the exceptional cases which arose via AD is the MSD gene of the sablefish, GsdfY (table 1).…”
Section: (C) Punctuated Equilibrium Versus Gradual Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, with only a handful of exceptions (4 out of 12, table 1), the great majority of MSD genes belonging to the TGF-β family pathway arose via GD (table 1). Under this scenario, following a sudden duplication event, gradual neutral processes are thought to act on the dispensable gene copy (see the documented example of Dmrt1bY in medaka for instance, [15,48,49]). One of the exceptional cases which arose via AD is the MSD gene of the sablefish, GsdfY (table 1).…”
Section: (C) Punctuated Equilibrium Versus Gradual Transformationmentioning
confidence: 99%
“…If only the final gene product of a regulatory network produces a phenotype, then changes in the upstream system can occur without necessarily impacting the final phenotype, and thus can evolve neutrally [12,13]. Furthermore, since downstream genes of sex-determining pathways seem to be more conserved than upstream ones, it was hypothesized that the SD cascade is built from a 'bottom-up' scenario, with novel top regulators being issued from downstream components of the cascade itself ( [14] and this issue [15] for a revisit of that theory).…”
Section: Introductionmentioning
confidence: 99%
“…Adolfi et al . [ 89 ] argue that coevolution between a new sex-determining locus and other members of this network is required to restrict the function of the sex-determining locus to sex determination without negatively affecting other steps of sex differentiation and reproductive roles. Such changes can be an important pre-condition for the emergence of a new sex-determining trigger.…”
Section: Where Do Sex-determining Loci Come From?mentioning
confidence: 99%
“…The detailed analysis of the relatively young sexdetermining gene in medaka, Oryzias latipes, representing a radiation with evolutionarily unstable sex determination [72,73], revealed that the function of a new master sex-determining gene required several changes and substantial rewiring of interactions among members of the gonadal differentiation networks [55]. Adolfi et al [89] argue that coevolution between a new sex-determining locus and other members of this network is required to restrict the function of the sex-determining locus to sex determination without negatively affecting other steps of sex differentiation and reproductive roles. Such changes can be an important precondition for the emergence of a new sex-determining trigger.…”
mentioning
confidence: 99%
“…-Sex determination without sex chromosomes and/or governed by epigenetics [5,6]; -Origin of sex-determining genes [7][8][9]; -Reasons for differentiation of sex chromosomes and differences in their rates of differentiation [10][11][12][13][14].…”
mentioning
confidence: 99%